PENGARUH PENGGUNAAN MEDIA CAMTASIA TERHADAP HASIL BELAJAR MATEMATIKA DI SDN 2 TROSO JEPARA - Felinna Kharissatun; Aan Widiyono (STKIP Melawi, 2022)
Abstract: The purpose of this study was to determine the effect of using Camtasia videos on mathematics learning outcomes at SDN 2 Troso Jepara in the 2020/2021 academic year. The method used is quantitative research with a quasi-experimental type one group pretest-posttest design. The sample of this study amounted to 38 students of class V SDN 2 Troso Jepara. The test data for learning outcomes is in the form of multiple choice with a total of 25 questions. Analysis of the data used is kolmogorof-Smirnov and t-test. The use of Camtasia media shows that there is a significant difference in student learning outcomes between the pretest and posttest in mathematics problem solving materials. Judging from the mean value of the pretest of students was 56.74, while the mean value of the posttest was 77.79. The increase in the pretest and posttest scores was 21.05. The results of this analysis can be concluded that the use of camtasia media is very effective because it can improve mathematics learning outcomes.Keywords: camtasia media, mathematics, learning outcomes Abstrak: Tujuan dari penelitian ini yaitu mengetahui pengaruh dari penggunaan video camtasia terhadap hasil belajar matematika di SDN 2 Troso Jepara tahun ajaran 2020/2021. Metode yang digunakan yaitu penelitian kuantitatif dengan jenis quasi eksperimen tipe one grup pretest-posttest design. Sampel penelitian ini berjumlah 38 siswa kelas V SDN 2 Troso Jepara. Data tes hasil belajar berbentuk multiple choice sejumlah 25 soal. Analisis data yang digunakan adalah kolmogorof-smirnov dan uji-t. Dengan penggunaan media camtasia menunjukkan bahwa terdapat perbedaan nyata tentang hasil belajar siswa antara pretest dan posttest pada materi materi pemecahan masalah matematika. Dilihat dari nilai rerata pretest siswa sebesar 56,74 sedangkan, nilai rerata posttest sebesar 77,79. Kenaikan nilai pretest dan posttest sebesar 21,05. Hasil analisis ini dapat disimpulkan bahwa penggunaan media camtasia sangat efektif digunakan karena dapat meningkatkan hasil belajar matematika.Kata Kunci: media camtasia, matematika, hasil belajar